Wanprestasi Dalam Perjanjian Pinjam Meminjam Uang Di Kopersi Pondok Pesantren Al-Mutma’innah Kediri - Lalu Rival Brajanegara; Aris Munandar (Private Law, 2023)
This study aims to find out and explain the loan and borrowing agreement implementation at the AL-Mutmainnah Islamic Boarding School Cooperative and the settlement of disputes in the event of default in the loan-borrowing agreement. The research method in empirical normative writing. The study results found that the loan agreement was implemented as a standard agreement outlined in the agreement letter. The form of dispute resolution in the loan and loan agreement belonging to the AL-Mutmainnah Islamic Boarding School Cooperative is by way of dispute resolution outside the court (non-litigation), negotiation, and mediation, which is carried out deliberation to reach consensus, or through kinship that directly involves both parties.